Analisis Motivasi Kerja dan Kedisiplinan Terhadap Kinerja Pegawai - Hartadi, Agung; Nugroho, Nurhadi (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2024)
The purpose of this research is to partially determine the influence of work motivation and discipline on employee performance at the Gunungkidul District Health Service. And to find out work motivation and discipline simultaneously influence employee performance at the Gunungkidul District Health Service. This analysis uses independent variables, namely work motivation (X1) and discipline (X2), while the dependent variable is employee performance (Y). The research method uses quantitative methods in the form of statistical data. The population used was all employees in a sector of the Gunungkidul District Health Service with a saturated sample. Based on the results of data processing SPSS for Windows version 17. Work motivation variable (X1) with a calculated t value of 3.260 > t table 2.048, this means that variable X1 has an influence on Y and the discipline variable (X2) with a calculated t value of 1.640 < t table 2.048 p. This means that there is no partial influence on (Y). And from the calculation results, the variables work motivation (X1) and discipline (X2) are obtained with calculated F 28.098 > F table 4.21. This shows that these two variables simultaneously influence employee performance (Y), and have a contribution value of 65.1% and the remaining 34.9% is influenced by other variables.